Schwartz–Jampel syndrome - Chandra, Sadanandavalli Retnaswami (J Pediatr Neurosci, 2015)
Schwartz–Jampel syndrome is a very rare congenital myotonic syndrome with typical phenotypic and electrophysiological features. Diagnosis is made by awareness into the typical phenotypic characters.